PERJANJIAN SEBAGAI PERWUJUDAN LAW AS A TOOL OF SOCIAL ENGINEERING - Utama, Erry Praditya; Bangun, Cendera Rizky Anugrah (IBLAM LAW REVIEW, 2023)
Agreements are a legal instrument that functions as an instrument of social control (Law as a Tool of Social Engineering), especially regarding community economic activities. The principle of the agreement is freedom of contract and once the agreement is agreed upon, it has the force of law for the parties who agree to it (Pacta Sunt Servanda). This is where the function of the Agreement is to ensure that the promising parties do not violate their promises. Agreements can be made verbally or in writing, but for legal certainty, ideally they should be made in writing. An ideal agreement is made with reference to legal objectives, namely justice, benefit and legal certainty. If the agreement is carried out in accordance with the law in every economic transaction in society, the function of the agreement as Law as a Tool of Social Engineering will be realized. However, unfortunately there are obstacles to effective implementation, one of which is public awareness regarding agreement procedures. Proper communication is a supporting factor for the effective implementation of contract law. So it is very important for the role of government and professionals to increase the public's understanding and positive perception, especially regarding agreement procedures and in general regarding the law. Perjanjian adalah salah satu instrumen hukum yang berfungsi sebagai instrumen kontrol sosial (Law as a Tool of Social Engineering) khususnya terkait aktifitas ekonomi masyarakat. Asas perjanjian adalah kebebasan berkontrak dan setelah perjanjian disepakati maka kekuatannya layaknya undang-undang bagi para pihak yang menyepakatinya (Pacta Sunt Servanda). Di sinilah fungsi Perjanjian untuk memastikan para pihak yang berjanji untuk tidak melanggar janjinya. Perjanjian dapat dibuat secara lisan atau tertulis, namun untuk kepastian hukum, idealnya dibuat tertulis. Perjanjian yang ideal, dibuat dengan mengacu pada Tujuan Hukum yaitu Keadilan, Kemanfaatan dan Kepastian Hukum. Apabila perjanjian dijalankan dengan sesuai Hukum pada setiap transaksi ekonomi masyarakat maka terwujudlah fungsi perjanjian sebagai Law as a Tool of Social Engineering. Namun sayangnya ada saja hambatan untuk implementasi yang efektif, salah satunya adalah awareness dari masyarakat terkait prosedur perjanjian. Komunikasi yang tepat menjadi faktor pendukung implementasi hukum perjanjian yang efektif. Sehingga penting sekali peran dari pemerintah dan professional untuk meningkatkan pemahaman dan persepsi positif masyrakat khususnya terhadap prosedur perjanjian dan secara umum terhadap hukum